2014
DOI: 10.15288/jsad.2014.75.428
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Motives and Links to Alcohol Use in 13 European Countries

Abstract: ABSTRACT. Objective:The purpose of this study was to test the structure and endorsement of drinking motives and their links to alcohol use among 11-to 19-year-olds from 13 European countries. Method: Confi rmatory factor analysis, latent growth curves, and multiple regression models were conducted, based on a sample of 33,813 alcohol-using students from Belgium, Denmark, Estonia, Finland, Hungary, Ireland, Italy, Poland, Portugal, Scotland, Slovakia, Switzerland, and Wales who completed the Drinking Motives Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
140
4
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(181 citation statements)
references
References 39 publications
18
140
4
15
Order By: Relevance
“…The former shows that the negative association of conformity motives with alcohol use repeatedly found in cross-sectional studies 10,14,40 is also true over time. This indicates that small amounts of alcohol already fulfill the function of fitting in with a group and not feeling left out; consumption of high amounts on such occasions may actually be counterproductive.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The former shows that the negative association of conformity motives with alcohol use repeatedly found in cross-sectional studies 10,14,40 is also true over time. This indicates that small amounts of alcohol already fulfill the function of fitting in with a group and not feeling left out; consumption of high amounts on such occasions may actually be counterproductive.…”
Section: Discussionmentioning
confidence: 76%
“…Firstly, the consistent reciprocal links between social and enhancement motives over time may indicate that drinking for social and enhancement motives is not only strongly correlated in adolescence 10,20,29,40 but that these behaviors also appear to amplify each other during early adulthood. Secondly, social motives at t 0 predicted an increase in coping motives, indicating a possible transition for some people from drinking mainly at parties, celebrations and social gatherings, the most commonly indicated drinking motive of adolescents, 29,40 to drinking to alleviate problems and worries. Thirdly, coping motives at t 0 predicted a decrease in enhancement motives, suggesting that those who already scored high on coping drinking motives before 20 years of age might lose their enjoyment of drinking over time.…”
Section: Discussionmentioning
confidence: 99%
“…To initiate drinking, and to gradually increase one's alcohol consumption, may be considered normative behaviour in this developmental period. Moreover, adolescents most often drink for social and enjoyment reasons [28,51], and one may assume that drinking to relieve emotional distress is relatively more prevalent among older and more experienced drinkers. Indeed, Cooper et al's [52] longitudinal study showed that selfmedication motives for drinking were reported gradually more often during the transition from adolescence into early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that coping is a frequent motive for the consumption of alcohol [16]. Forthcoming studies can evaluate alcohol consumption and its relationship to stressors and coping strategies as confounding factors.…”
Section: Discussionmentioning
confidence: 99%